Social Network Analysis on the Driver Partner Application for Home Culinary Entrepreneurs - Wahyu Nurul Faroh; Sri Eka Lestari (Publisher Cv. Inara, 2021)
Technology implementation is becoming more prevalent nowadays. This, of course, makes it easier for entrepreneurs in marketing, sales, and the ease of establishing communication with potential buyers. However, it is not automatically able to be fully utilized. There are still many entrepreneurs who know about it but do not know-how and use it to increase sales. For this reason, this study will analyze how the effectiveness of using a simple application, which involves driver-partners in maximizing sales. This research will begin by crawling data on social networks, then withdrawing data from social network importers using Gephi, and then analyzing it using Social Network Analysis.